THE SELF-ESTIMATION OF THE HEALTH LEVEL, PHYSICAL ACTIVITIES AND FEELING OF THE RIGA BASIC SCHOOL STUDENTS AND UNIVERSITY PEDAGOGICAL SPECIALTY STUDENTS - Porozovs, Juris; Dudkina, Aija; Valdemiers, Alvis (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
Students is a group of population, who experience psychological overload and emotional strain. These factors could have a negative impact on student's health, but good health level and positive mood are important factors for high learning outcomes. The survey of Riga 2nd Gymnasium 9th grade basic school students and University of Latvia 1st course pedagogical speciality students was carried out. The self-estimation of health level, physical activities and feeling at school and at home of the both group students was compared. The results of the survey showed that the majority of students have good health level or they have minor health problems. Physical activity of basic school students is higher than the physical activity of university students. A part of students regularly experience strain. More basic school students in comparison with university students are regularly in the state of stress. Overall university students feel better at university than basic school students at school. The majority of both group students feel good at home. Students consider that important factors for maintaining of the health are: correct sleep regimen, proper nutrition regime, enough physical activities, avoiding from stress and overload.